Anchorman : the legend of Ron Burgundy [videorecording (Blu-Ray)] - McKay, Adam, 1968-; Ferrell, Will, 1967-; Apatow, Judd, 1967-; Applegate, Christina, 1971-; Rudd, Paul (DreamWorks Pictures : [Distributed by] Paramount Home Entertainment, 2011)
Ron Burgundy is a top anchorman in the '70s. When feminism marches into the newsroom in the form of Veronica, he is okay as long as she covers 'female issues.' When she steps behind the news desk, it becomes more than a battle, it's war. Special features include: commentary, bloopers, deleted and extended Scenes, and more.